2019
DOI: 10.1177/0145561319881571
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory Bulb Volume and Olfactory Sulcus Depth in Patients With OSA: An MRI Evaluation

Abstract: Objectives: We evaluated olfactory functions in patients with obstructive sleep apnea (OSA). Methods: The cranial magnetic resonance images of 58 adult patients (36 males and 22 females) aged 27 to 79 years were retrieved from the hospital picture archiving and communication system (PACS) system. There were 29 patients with OSA (17 males and 12 females), diagnosed according to the polysomnography results. A control group consisted of 29 healthy patients without OSA. Olfactory bulb (OB) volume and olfactory sul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…2,19 In these studies, prolonged exposure to hypoxia can induce reduction in the number of olfactory neurons, which could be related to the damage of olfactory bulb in patients with OSA due of CIH. 19 Furthermore, despite the evidence of anatomical alterations in the olfactory system and functional changes in other neural circuits, induced by CIH, the specific effects of CIH on olfactory function have been directly assessed in other studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2,19 In these studies, prolonged exposure to hypoxia can induce reduction in the number of olfactory neurons, which could be related to the damage of olfactory bulb in patients with OSA due of CIH. 19 Furthermore, despite the evidence of anatomical alterations in the olfactory system and functional changes in other neural circuits, induced by CIH, the specific effects of CIH on olfactory function have been directly assessed in other studies.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18] Olfactory bulb volumes in the OSA group were significantly lower than those in the control group in some studies. 2,19 In these studies, prolonged exposure to hypoxia can induce reduction in the number of olfactory neurons, which could be related to the damage of olfactory bulb in patients with OSA due of CIH. 19 Furthermore, despite the evidence of anatomical alterations in the olfactory system and functional CNPase mRNA levels in the brain tissue were evaluated using RT-PCR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Altogether this indicates the potential for applying this automated method in clinical settings in which olfactory bulb volume is relevant, for example in patients with depression ( Rottstaedt et al, 2018a ; Rottstaedt, Weidner, Hummel, & Croy, 2018b ), schizophrenia ( Asal et al, 2018 , Nguyen et al, 2011 ) or neurodegenerative diseases ( Marin et al, 2018 , Thomann et al, 2009 ). However, olfactory bulb volume is not only relevant for diseases that are primarily related to the brain; there is also evidence that it can be of clinical relevance in other patients, such as patients with obstructive sleep apnea ( Doğan et al, 2020 ), patients with obesity ( Karaoglan and Colakoglu Er, 2020 , Poessel et al, 2020 ). In addition, current studies showed that olfactory loss due to a COVID-19 infection can lead to atrophy of the olfactory bulb volume ( Chiu et al, 2021 , Tsivgoulis et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…To measure OS depth, we examined coronal T2weighted SPIR sequence sections, and drew a virtual line connecting the "inferior orbital gyrus and gyrus recti in the posterior plane of the orbit." Then, we drew a perpendicular line from this point to the deepest point of the OS and measured the length of this line; this value represents OS depth and was recorded in millimeters 4,5 .…”
Section: Peripheral Olfactory Areasmentioning
confidence: 99%